Annealing and TMOS coating on PSF/ZTC mixed matrix membrane for enhanced CO2/CH4 and H2/CH4 separation. Issue 6 (22nd June 2022) - Widiastuti, Nurul; Caralin, Irmariza Shafitri; Widyanto, Alvin Rahmad; Wijiyanti, Rika; Gunawan, Triyanda; Karim, Zulhairun Abdul; Nomura, Mikihiro; Yoshida, Yuki
Abstract : Recently, natural gas (mostly methane) is frequently used as fuel, while hydrogen is a promising renewable energy source. However, each gas produced contains impurity gases. As a result, membrane separation is required. The mixed matrix membrane (MMM) is a promising membrane. The huge surface area and well-defined pore structure of zeolite templated carbon (ZTC)-based MMM allow for effective separation. However, the interfacial vacuum in MMM is difficult to avoid, contributing to poor separation performance. This research tries to improve separation performance by altering membrane surfaces. MMM PSF/ZTC was modified by annealing at 120, 150, and 190°C; coating using 0.01, 0.03, and 0.05 mol tetramethyl orthosilicate (TMOS); and a combination of both, i.e. annealing at 190°C and coating using 0.03 mol TMOS. MMM PSF/ZTC successfully significantly improved CO2 /CH4 selectivity by a combination of annealing at 190°C and coating 0.03 mol TMOS from 1.37 to 5.90 (331%), and H2 /CH4 selectivity by coating with 0.03 mol TMOS from 4.58 to 65.76 (1378%). The enhancement of selectivity was due to structural changes to the membrane that became denser and smoother, which SEM and AFM observed. In this study, annealing and coating treatments are the methods investigated for improving the polymer matrix and filler particle adhesion.